Meningkatkan Kesadaran Lingkungan Dalam Pengelolaan Sampah Berdasarkan Perspektif Theology of Hope Jürgen Moltmann - Kapoh, Gabriela Veren; Masambe, Helen Gratia; Timbuleng, Nontje Mery (Jurnal Teologi Pambelum, 2025)
This study presents a waste management intervention model based on Jürgen Moltmann’s Theology of Hope at the GMIM Sion Woloan congregation in the Tomohon Two region. Employing a qualitative approach, data were collected through observation, documentation, interviews, and literature review, then analyzed descriptively. The results indicate that although theological motivation regarding the importance of reduction, separation, and recycling has been conveyed in sermons by designated ministers, actual practices in the field have yet to be implemented. This is also underpinned by a lack of segregated facilities, technical understanding, and cross-sector synergy. Therefore, the formulation of an integrated homiletics of hope, enhancements to infrastructure, and partnerships with government bodies and recycling institutions are key to realizing a sustainable ecological liturgy. These findings affirm that eschatological hope can mobilize the congregation to care for creation in concrete ways.